2020
DOI: 10.4995/var.2020.12416
|View full text |Cite
|
Sign up to set email alerts
|

HBIM, 3D drawing and virtual reality for archaeological sites and ancient ruins

Abstract: <p class="VARAbstract">Data collection, documentation and analysis of the traces of ancient ruins and archaeological sites represent an inestimable value to be handed down to future generations. Thanks to the development of new technologies in the field of computer graphics, Building Information Modelling (BIM), Virtual Reality (VR) and three-dimensional (3D) digital survey, this research proposes new levels of interactivity between users and virtual environments capable of communicating the tang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 46 publications
0
56
0
4
Order By: Relevance
“…Accordingly, the standard should therefore represent the state of the art, practice and science shared by all stakeholders (private and public), concerning a specific process, service, or product. In this context, interesting studies have identified the main shortcomings of these guidelines oriented to new buildings and proposed their methods able to improve HBIM projects (Banfi, 2020;.…”
Section: The Era Of Standardization and Bim Interoperabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the standard should therefore represent the state of the art, practice and science shared by all stakeholders (private and public), concerning a specific process, service, or product. In this context, interesting studies have identified the main shortcomings of these guidelines oriented to new buildings and proposed their methods able to improve HBIM projects (Banfi, 2020;.…”
Section: The Era Of Standardization and Bim Interoperabilitymentioning
confidence: 99%
“…In recent years, interesting studies proposed digital workflows able to manage the richness of heritage buildings through very detailed HBIM projects. Unlike digital representations of newly built buildings, HBIM was useful for investigating new types of analyses such as material analyzes (Brumana et al, 2018), construction site conservation projects (Fai, & Rafeiro, 2014), work breakdown structures (WBS) (Putra Lim, & Latief, 2020), mixed reality and archaeological sites (Banfi, 2020), infrastructures (Boykov, Skvortsov, & Gurev, 2020), and finite element analysis (FEA) (Fabozzi et al, 2020). In this context, thanks to specific exchange formats have been possible to transform geometric entities such as solids, surfaces, and primitives for different types of BIM-based analyses.…”
Section: Toward a Scan-to-hbim Process: From Point Clouds To Accurate Informative Modelsmentioning
confidence: 99%
“…3 Carlo III bridge, Moiano (BN), aerial image showing the crossing of the Isclero river Fig. 4 The main materials of the Bridge: a the local limestone with the presence of a disintegration phenomenon and a superficial patina; b the yellow tuff, and the clear lesion on the South elevation fields, and many tweaks have been proposed to address this issue (Banfi 2020).…”
Section: Bim Modelling and Thematic Mapsmentioning
confidence: 99%
“…These issues are often caused by the dimension of the file associated with this reality-based models and with the complexity of their topology. Due to the lack of advanced modelling tools in many BIM applications, that provide management tools for new buildings rather than pre-existing heritage assets (Banfi 2020), frequently a substantial simplification of the acquired geometries is required. This aspect is a crucial point since in the framework of cultural heritage documentation, a high level of detail is not only recommended but almost mandatory, due to the necessity to accurately and adequately study the shapes, geometries, features and irregularities of the researched objects.…”
Section: Hbim and Restorationmentioning
confidence: 99%